Diagnóstico situacional dos apicultores e meliponicultores no contexto da agricultura familiar da mesorregião oeste do Rio Grande do Norte - Pereira, Daison de Castilhos (Universidade Federal Rural do Semi-Árido, 2014)
The problem of keeping people in countryside has always been subject of studies and endless discussions in socio-political context in Brazil. With the development of productive chain and volatility in supplying labor hand with little or no specialization, diversification of family farming has emerged as an option to increasing the attachment of man to the field. In Caatinga biome, however, the weather conditions are unfavorable, requiring to searching for multiple alternatives. Apiculture (beekeeping of the genus Apis, Apis mellifera) and meliponiculture (beekeeping of native, stingless bees) emerged as optional activity to raise the income of small farmers. Our approach to this problem, in west mesorregion of Rio Grande do Norte, was to comparing two sub-samples, traditional farmers and beekeepers/stingless beekeepers, portrayed by their socioeconomic conditions. Data from survey "Sebrae/RN in Semiarid - Situational Diagnosis of Rural Entrepreneur" were used for the development and analysis of this research, applied during the second half of 2012, when 1160 small farmers were interviewed. A sample of 94 questionnaires was provided. New interviews were conducted in May and August 2013, for confirmation and upgrade, with the same sample of respondents. Environmental, social and technological information that directly or indirectly affect family farming were processed and analyzed. No evidences of differences between farmers and beekeepers in variables gender, education and age were found, however male predominance is evident, for schooling only beekeepers have higher level education and age group is concentrated above forty years old. It was observed that on financial variables beekeepers and stingless beekeepers are not prepared for adverse situations of environmental or social causes. The honey production is undergoing a period of decline due to prolonged drought and excessive heat inside beehives. It was concluded that beekeepers and stingless beekeepers go through difficulties of force majeure and fortuitous event and honeybee activity can raise the income of family farming if conducted in a methodic and rational manner, with proper training and management for each considered species Apis or Melipona
Situational diagnosis of beekeepers and stingless beekeepers in the context of family farming on west mesorregion of Rio Grande do Norte, Brazil
Keywords: Family farming; beekeeping; Mesoregion west - Rio Grande do Norte; Meliponiculture; Agricultura familiar; Apicultura; Mesorregião oeste do Rio Grande do Norte; Meliponicultura; MULTIDISCIPLINAR::CIENCIAS AMBIENTAIS::AMBIENTE, TECNOLOGIA E SOCIEDADE